2009
DOI: 10.1128/jcm.01449-08
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Clinically Relevant Nonhemolytic Streptococci on the Basis of Sequence Analysis of 16S-23S Intergenic Spacer Region and Partial gdh Gene

Abstract: Nonhemolytic streptococci (NHS) cause serious infections, such as endocarditis and septicemia. Many conventional phenotypic methods are insufficient for the identification of bacteria in this group to the species level. Genetic analysis has revealed that single-gene analysis is insufficient for the identification of all species in this group of bacteria. The aim of the present study was to establish a method based on sequence analysis of the 16S-23S intergenic spacer (ITS) region and the partial gdh gene to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 45 publications
1
28
1
Order By: Relevance
“…Thus, evidence of exchange of homologous gene sequences between species invalidates the many suggested identification procedures based on sequence comparisons of single housekeeping genes such as sodA, gdh, rpoA, recA, recN, etc. (11,12,22,28,31,34,41).…”
mentioning
confidence: 99%
“…Thus, evidence of exchange of homologous gene sequences between species invalidates the many suggested identification procedures based on sequence comparisons of single housekeeping genes such as sodA, gdh, rpoA, recA, recN, etc. (11,12,22,28,31,34,41).…”
mentioning
confidence: 99%
“…Other molecular-based identification methods for VGS species assignment have employed single-gene targets, such as rpoA, rpoB, rnpB, rodA, sodA, and gdh, with varied success (8,(17)(18)(19)(20)(21)(22)(23)(24). Although a single-gene approach is practical, problems with singlegene techniques in VGS stem from a highly diverse population undergoing extensive rates of inter-and intraspecies homologous recombination and horizontal gene transfer, which minimizes the utility of identification procedures based on any one particular gene tested to date (3,8,9,(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…However, it involves more inputs and selection of other genes out of a few thousand genes within the genome is not an easy task. In spite of the fact that around 23 genes have been used frequently in many studies carried out for identifying Streptococcus, no consensus gene has been identified [3,4,11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. It has also not been realized that except recA, the rest of the 22 genes are not present in all the species of Streptococcus.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus poses a big challenge as most pathogenic strains are genetically very close to each other and have multiple copies of rrs per genome. A few genes which are frequently used for the identification of Streptococcus include genes: cpsA, gdh, groESL, lytA, ply, psaA, pspA, recA, recN, rpoA, rpoB, sodA, tuf, wzg, 16S-23S ribosomal DNA spacer region, and the DNA fragment Spn9802 [3,4,11,[22][23][24][25][26][27][28][29][30][31]. Optochin susceptibility testing (CO 2 atmosphere) in combination with amplification of Spn9802 fragment and the autolysin genes: lytA, rpoB, and tuf, have proved effective in identifying S. pneumoniae [32].…”
Section: Introductionmentioning
confidence: 99%